The Periodic Table needs negative orbitals in order to eliminate quantum weirdness: a new quantum chemistry mathematics : A new quantum chemistry mathematics - Jeffrey H. Boyd (JOURNAL OF ADVANCES IN CHEMISTRY, 2020)
A consensus among quantum experts is that the quantum world is not properly understood. It is a mistake to think we can cure quantum weirdness by tinkering with superficial aspects of quantum mechanics (QM). We propose that nature uses (–ψ) as its wave function, whereas QM uses (+ψ). We propose therefore that the Periodical Table should be changed to negative orbitals (–ψ). Surprisingly, this change makes almost no difference to chemistry on a practical level. The Born rule takes the absolute square of an amplitude to obtain a probability to test in chemistry lab P=|–ψ|2=|+ψ|2. We propose a new math based on (–ψ) that is the mirror image of quantum mathematics. We call it the Theory of Elementary Waves (TEW). The negative sign is not an electrical charge. It has nothing to do with Coulomb’s law. Valence electrons are unchanged. Ions, covalent bonds, dipoles, metals, hydrogen bonding and the hydrogen 21 cm line are unchanged. The octet rule and rules for drawing dot structures of molecules do not change. Amino acids, sugars and DNA do not change their handedness. We cite abundant experimental evidence showing that TEW is correct and QM is wrong.